Clinical-Genetic Features Influencing Disability in Spastic Paraplegia Type 4: A Cross-sectional Study by the Italian DAISY Network. (30th April 2022) - Rossi, Salvatore; Rubegni, Anna; Riso, Vittorio; Barghigiani, Melissa; Bassi, Maria Teresa; Battini, Roberta; Bertini, Enrico; Cereda, Cristina; Cioffi, Ettore; Criscuolo, Chiara; Dal Fabbro, Beatrice; Dato, Clemente; et al.
Abstract : Background and Objectives: Hereditary spastic paraplegias (HSPs) are a group of inherited rare neurologic disorders characterized by length-dependent degeneration of the corticospinal tracts and dorsal columns, whose prominent clinical feature is represented by spastic gait. Spastic paraplegia type 4 (SPG4, SPAST-HSP) is the most common form. We present both clinical and molecular findings of a large cohort of patients, with the aim of (1) defining the clinical spectrum of SPAST-HSP in Italy; (2) describing their molecular features; and (3) assessing genotype-phenotype correlations to identify features associated with worse disability. Methods: A cross-sectional retrospective study with molecular and clinical data collected in an anonymized database was performed. Results: A total of 723 Italian patients with SPAST-HSP (58% men) from 316 families, with a median age at onset of 35 years, were included. Penetrance was 97.8%, with men showing higher Spastic Paraplegia Rating Scale (SPRS) scores (19.67 ± 12.58 vs 16.15 ± 12.61, p = 0.009). In 26.6% of patients with SPAST-HSP, we observed a complicated phenotype, mainly including intellectual disability (8%), polyneuropathy (6.7%), and cognitive decline (6.5%). Late-onset cases seemed to progress more rapidly, and patients with a longer disease course displayed a more severe neurologic disability, with higher SPATAX (3.61 ± 1.46 vs 2.71 ± 1.20, p < 0.001) and SPRS scores (22.63 ± 11.81 vs 12.40 ± 8.83, p < 0.001). Overall, 186 different variants in the SPAST gene were recorded, of which 48 were novel. Patients with SPAST-HSP harboring missense variants displayed intellectual disability (14.5% vs 4.4%, p < 0.001) more frequently, whereas patients with truncating variants presented more commonly cognitive decline (9.7% vs 2.6%, p = 0.001), cerebral atrophy (11.2% vs 3.4%, p = 0.003), lower limb spasticity (61.5% vs 44.5%), urinary symptoms (50.0% vs 31.3%, p < 0.001), and sensorimotor polyneuropathy (11.1% vs 1.1%, p < 0.001). Increasing disease duration (DD) and abnormal motor evoked potentials (MEPs) were also associated with increased likelihood of worse disability (SPATAX score>3). Discussion: The SPAST-HSP phenotypic spectrum in Italian patients confirms a predominantly pure form of HSP with mild-to-moderate disability in 75% of cases, and slight prevalence of men, who appeared more severely affected. Early-onset cases with intellectual disability were more frequent among patients carrying missense SPAST variants, whereas patients with truncating variants showed a more complicated disease. Both longer DD and altered MEPs are associated with worse disability.